Climatology of Upper Tropospheric–Lower Stratospheric (UTLS) Jets and Tropopauses in MERRA - Manney, Gloria L.; Hegglin, Michaela I.; Daffer, William H.; Schwartz, Michael H.; Santee, Michelle L.; Pawson, Steven (Journal of Climate, 2014)
A global climatology (1979–2012) from the Modern-Era Retrospective Analysis for Research and Applications (MERRA) shows distributions and seasonal evolution of upper tropospheric jets and their relationships to the stratospheric subvortex and multiple tropopauses. The overall climatological patterns of upper tropospheric jets confirm those seen in previous studies, indicating accurate representation of jet stream dynamics in MERRA. The analysis shows a Northern Hemisphere (NH) upper tropospheric jet stretching nearly zonally from the mid-Atlantic across Africa and Asia. In winter–spring, this jet splits over the eastern Pacific, merges again over eastern North America, and then shifts poleward over the North Atlantic. The jets associated with tropical circulations are also captured, with upper tropospheric westerlies demarking cyclonic flow downstream from the Australian and Asian monsoon anticyclones and associated easterly jets. Multiple tropopauses associated with the thermal tropopause “break” commonly extend poleward from the subtropical upper tropospheric jet. In Southern Hemisphere (SH) summer, the tropopause break, along with a poleward-stretching secondary tropopause, often occurs across the tropical westerly jet downstream of the Australian monsoon region. SH high-latitude multiple tropopauses, nearly ubiquitous in June–July, are associated with the unique polar winter thermal structure. High-latitude multiple tropopauses in NH fall–winter are, however, sometimes associated with poleward-shifted upper tropospheric jets. The SH subvortex jet extends down near the level of the subtropical jet core in winter and spring. Most SH subvortex jets merge with an upper tropospheric jet between May and December; although much less persistent than in the SH, merged NH subvortex jets are common between November and April.